AN Empirical Model of OCB as an Intervening Variable on Performance - Trias Setyowati; Fefi Nurdiana Wijayanti; Holise (IECON: International Economics and Business Conference, 2025)
This study aims to examine both the direct and indirect effects of organizational culture (X1) and organizational climate (X2) on employee performance, with Organizational Citizenship Behavior (OCB) acting as an intervening variable. The issue underlying this research is that existing data and observations indicate that lecturers' performance has not yet reached its full potential, particularly in fulfilling the Tri Dharma of higher education. The implementation of the Tri Dharma – a key benchmark for lecturers’ performance – reflects individual effectiveness and directly impacts institutional outcomes. Suboptimal performance among lecturers can be observed through their performance indicators, signaling the need to explore the underlying factors influencing their work outcomes. This study surveyed 200 lecturers from Muhammadiyah universities across East Java. Data were collected through questionnaires and interviews, with participants selected using a simple random sampling method via lottery. The data were then analyzed using descriptive statistics, Structural Equation Modeling (SEM) with AMOS software, and the Sobel test. The results show that although organizational culture has a positive influence on performance, the effect is not statistically significant. In contrast, organizational climate has a significant positive effect on performance. Moreover, organizational culture significantly and positively influences OCB, which in turn significantly enhances performance. The study also finds that both organizational culture and climate have significant indirect effects on performance when mediated by OCB.